TEACHING ENVIRONMENTAL AWARENESS THROUGH ENGLISH LESSONS - Umarova Dilshoda (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Today, environmental problems such as climate change, pollution, and deforestation are becoming more serious around the world. Because of this, schools and teachers are trying to help students become more environmentally responsible. English lessons can play an important role in developing environmental awareness because language learning is closely connected with communication, discussion, reading, and critical thinking. English teachers can include environmental topics in speaking, reading, listening, and writing activities while also improving students’ language skills. This article discusses the importance of teaching environmental awareness through English lessons, effective classroom strategies, benefits for students, and some possible challenges. The article is based on reliable academic sources and studies related to English Language Teaching (ELT) and environmental education.